The Analysis of Illocutionary act in Rich Roll Podcast - Laras, I Made Aditya Laras; I Komang Sulatra (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2024)
This research examines illocutionary acts in the context of the Rich Roll's Podcast, focusing on the words spoken by renowned motivator David Goggins. The study aims to identify the most frequently used type of speech act and analyze their speech act arrangement throughout the podcast. Illocutionary acts go beyond literal meaning and encompass the speaker's intended effects, such as making promises, asking questions, giving orders, expressing opinions, making suggestions, and issuing apologies. The data source in this research was taken in Rich Roll Podcast with David Goggins as the guest of this podcast. The methodology that is used in this research is divided into 2 methods which are qualitative methods and quantitative methods. The data was supported by Searle's Theories that conveyed speech acts into 5 categories which are assertive, directive, commissive, expressive, and declarative. This data shows that the type of speech acts that don't exist from the data source are the Commissive and Directive Speech acts. Calculating the data in a total percentage can be shown as Assertive is 40%, Expressive is 46,7%, Declarative is 13,33% and 0% for Commissive and Directive.